Le Transperceneige et Snowpiercer : figuration, sas et espaces de transit(ion) - Tessa Sermet (ReS Futurae)
The graphic novel The Transperceneige and the movie Snowpiercer depicts societies forced to find refuge in a train after a climatic disaster. The train loses its function of transitional space to become a loco, the last habitable place on the planet. As a result, the relationship between the passengers / inhabitants of the train and the outside world changes, and the landscape becomes not much more than an image. The climate catastrophe also reinforces the exclusionary patterns put in place by the totalitarian system in power : the conjunction between (neo)capitalism and Anthropocene mainly affects the population in a marginal position, that is to say the ones confined in the rail cars. The disruptive movements of the tail-section revolutionaries towards the front are thus punctuated by multiple trials and rites of passages. Semiological and aesthetic features inherent to graphic novel and cinema (layout of boxes and panels, recurring passages, editing, shots, slow motion, music, etc.) transform these liminal steps into sas (airlocks in French), intermediate spaces that are not mere thresholds to cross. In the end, it seems that the train is itself a space of / in transition for a humanity in gestation.